ANALISIS DETERMINAN PROFITABILITAS PADA PERUSAHAAN CONSUMER CYCLICALS DI BURSA EFEK INDONESIA - Luh Vania Michaela (2022)
This research is a study that uses quantitative data which aims to determine the effect of Activity Ratio, Sales Growth, and Liquidity on Profitability. The population of this study is the consumer cyclicals sector using a saturated sample of 27 companies in the retail trade sub-sector during the 2017-2021 period. Data analysis in this study used Panel Data Analysis assisted by Microsoft Excel and E-views 12 with a significance level of 5%. The results of this study are that the Activity Ratio proxied by Working Capital Turnover (WCTO) has a negative effect on Profitability (ROA) while the Sales Growth and Liquidity (CR) variable has no effect on Profitability (ROA) Keywords : Profitability, Activity Ratio, Sales Growth, and Liquidity